2012
DOI: 10.2174/092986712798918770
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Targeting of Platelet-Mediated Cellular Interactions in Atherosclerosis and Inflammation

Abstract: Cellular interactions among platelets, leukocytes and endothelial cells are considered as a major cause of inflammation and atherosclerosis in many diseases. Via exposed surface receptors and released soluble substances, activated platelets play a crucial role in the initiation of inflammatory processes, resulting in endothelial injury and leading to formation of atherosclerotic plaque with possible thrombotic complications. Classic anti-platelet treatments (e.g. cyclooxygenase inhibitor or ADP-receptor antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…IL-1β, CD40 ligand (CD40L), β-thromboglobulin] are implicated in the development of atherosclerosis [41], [42], [43]. Recently, animal and (pre)clinical human studies have suggested that the two major platelet chemokines PF4 and RANTES, as well as CD40L, may be considered potential new candidates in the treatment of atherogenesis and inflammation [44]. Likewise, the SDF-1α/CXCR4 axis has been shown to be implicated in the mobilization and EPC homing [45].…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β, CD40 ligand (CD40L), β-thromboglobulin] are implicated in the development of atherosclerosis [41], [42], [43]. Recently, animal and (pre)clinical human studies have suggested that the two major platelet chemokines PF4 and RANTES, as well as CD40L, may be considered potential new candidates in the treatment of atherogenesis and inflammation [44]. Likewise, the SDF-1α/CXCR4 axis has been shown to be implicated in the mobilization and EPC homing [45].…”
Section: Discussionmentioning
confidence: 99%
“…For example, selectin-mediated adhesion of leukocytes to the BBB endothelial cells is a key event that contributes to neuroinflammation by facilitating transmigration of inflammatory cells into the brain tissue. Animal and human healthy volunteer studies have identified promising new selectin inhibitors, which might be clinically useful to prevent acute and chronic inflammation; reviewed (Nagy et al 2012). Indeed, clinical trial of a selectin inhibitor has shown promising results in patients with asthma where it reduced airway recruitment of eosinophils (Romano 2005).…”
Section: Therapeutic Implications Of An Immune/inflammation Link To Smentioning
confidence: 99%
“…The CD40-CD40L system is associated with both pro-thrombotic and pro-inflammatory effects. Soluble CD40L contributes to the pathophysiology of atherosclerosis and atherothrombosis [ 52 ]. Because of its autocrine, paracrine, and endocrine activities, sCD40L enhances platelet activation, aggregation, and platelet-leukocyte conjugation that may lead to atherothrombosis [ 13 , 53 , 54 ].…”
Section: What Is the Function Of Cd40l?mentioning
confidence: 99%